Judaeans under Persian Forced Labor and Migration Policies - Silverman, Jason M. (Anabasis. Studia Classica et Orientalia, 2015)
The use of forced migration and forced labor by the Achaemenids has received almost no scholarly attention, despite hints that both were widely used strategies. Moreover, the implications of these strategies for the Judaean populations within the empire have also gone mostly unnoticed. To understand the relations of these two neglected issues it is necessary to reconstruct both some of the historical evidence for their use and their likely sociological impacts within the Persian Empire with (ethnic) populations at large. Since this would be a major undertaking, this paper primarily seeks to determine on the basis of sociological models of forced labor and migration what kinds of impact on Judaeans can be expected from a few Persian case studies, and which of these impacts are likely to be directly visible within literary traces (i.e., the Hebrew Bible). This discussion will proceed under three headings: building projects, military colonies, and the organization of minority (work) groups. The implications of these results for further research are then suggested.